Electrochemical synthesis and characterization of titania nanotube thin film - Lim, Ying Chin (2013)
Titania nanotubes (TNT) have gained increasing interest due to their high surface area, fewer interfacial grain boundaries and excellent charge transfer between interfaces; all are critical properties in photoelectrochemical and photocatalysis application. In this study, TNT thin film electrodes were synthesized by electrochemical anodisation of pure Ti in a standard two-electrode cell containing NH4F solution. Parameters affecting the morphological, structural and geometry of TNT were investigated in three different electrolytic medium namely the acidic aqueous solution (NH4F/H2O), mixture of aqueous-organic solution (NH4F/H2O/EG) and an organic neutral solution (NH4F/EG). The characteristic of TNT were analyzed using Field Emission Scanning Electron Microscopy (FESEM), X-ray Diffractometry (XRD), Transmission Electron Microscopy (TEM), Energy Dispersive X-ray Analysis (EDX) and UV Visible Diffuse Reflectance Spectroscopy (UV-DRS). Meanwhile, the photoelectrochemical responses of TNT were investigated using Liner Sweep Photovoltammetry (LSPV) and their photoefficiency was evaluated in 0.1 M KOH under UV illumination. The thermal stability of short TNT (400 nm in length) and its morphological, structural, optical and photoelectrochemical changes as a result of heat treatment at 200-800 oC were also studied. In NH4F/H2O electrolyte, sample morphology was affected by electrolyte pH and fluoride concentration whereby nanotubes dimensions and their growth rate can be manipulated via anodisation voltage, bath temperature, anodisation duration and the addition of EDTA. Voltage range and NH4F concentration used for TNT formation varied depending on the electrolytic medium used during anodisation. Higher voltage range could be used in NH4F/EG to obtain larger diameter and longer length tube. An optimum fluoride concentration is required to achieve well-defined and long tube as higher amount of F- leads to faster chemical dissolution. Choice of electrolytic medium also has an influence on the crystalline structure, regularity, morphology, elemental composition and band gap of TNT. XRD results showed that pure anatase phase was obtained in NH4F/EG/H2O and NH4F/EG solution while mixture of anatase and rutile co-existed for TNT prepared in NH4F/H2O solution. As opposed to irregular nanotubes with ripples formed in NH4F/H2O, regular and smooth TNT with variation in length were obtained in NH4F/EG. The as-anodised TNT is amorphous and transformed to anatase phase at 300 oC. Crystallization of anatase phase increases on elevating calcination temperature and rutile phase co-existed at 500 oC. TNT is thermally stable up to temperature < 600 oC, above which changes in morphology and dimensions of TNT occurred. Calcination of TNT at 500 oC appeared to be the most favorable condition to retain the nanotubular structure with desired crystal phase and photoelectrochemical properties. The morphology and geometry of the TNT are important factors influencing the photoelectrochemical response, with higher photocurrent response are generally associated with thicker layer of TNT. Photoefficiency for TNT synthesized in different electrolytes medium was tested under halogen and UV light illumination. Highest photoefficiency was obtained for TNT prepared in NH4/EG compared to those prepared in other electrolytes due to formation of longer length tube.